2017
DOI: 10.1111/1471-0307.12443
|View full text |Cite
|
Sign up to set email alerts
|

Comparative milk fatty acid analysis of different dairy species

Abstract: This study compared the fatty acid (FA) profile of milk from different dairy mammals: buffalo, camel, cow, goat and yak. Data from milk samples and reports in the literature were processed using principal component analysis. The results showed that camel milk contained the lowest levels of C4:0–C12:0 and highest levels of unsaturated fatty acids. Goat milk had the highest level of C8:0–C14:0 FA. Characteristic differences were observed for yak and buffalo milk, which differed from cow milk by their higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
4
9
2
Order By: Relevance
“…Goat milk has been previously reported to contain less OA under control diets [45], contain less OA only after dietary oil supplementation [44] or having similar concentrations to cow milk [49,50]. The latter has also been observed in the present study, although only in December goat milk had lower concentrations of OA.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Goat milk has been previously reported to contain less OA under control diets [45], contain less OA only after dietary oil supplementation [44] or having similar concentrations to cow milk [49,50]. The latter has also been observed in the present study, although only in December goat milk had lower concentrations of OA.…”
Section: Discussionsupporting
confidence: 82%
“…Although previous studies reported similar SFA concentrations between goat and cow milk [49,50], the present work found that goat milk contained more SFA. However, goat milk contained less C14:0 and C16:0 and more of the shorter chain SFA (with 6–12 atoms of carbon).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Docosahexaenoic acid (DHA, C22:6 ω3), eicosapentaenoic acid (EPA, C20:5 ω3), conjugated linoleic acid (CLA, C18:2), and trans ‐vaccenic acid (TVA, C18:1 t11) are examples of bioactive milk lipids (BML). Yang, Zheng, Wang, and Yang (2018) analyzed the main fatty acids from dairy cows. The consumption and the health benefits of BML have been extensively reviewed elsewhere (Fusaro et al, 2019; McCrorie, Keaveney, Wallace, Binns, & Livingstone, 2011).…”
Section: Introductionmentioning
confidence: 99%